Non-typeable Haemophilus Influenzae detection in the lower airways of patients with lung cancer and chronic obstructive pulmonary disease - Sriram, Krishna B. (Multidisciplinary Respiratory Medicine, 2019)
Background: Chronic airway inflammation and hypersensitivity to bacterial infection may contribute to lung cancer pathogenesis. Previous studies have demonstrated that nontypeable Haemophilus influenzae (NTHi) is the most common colonizing bacteria in the lower airways of patients with COPD. The objective of this study was to determine the presence of NTHi and immunoglobulin concentrations in patients with lung cancer, COPD and controls. Methods: Serum and bronchial wash samples were collected from patients undergoing diagnostic bronchoscopy. Total IgE, IgG and specific NTHi IgG were measured by enzyme linked immunosorbent assay. Bronchial wash samples were examined for the presence of NTHi via PCR. Results: Out of the 60 patients: 20 had confirmed Lung Cancer, 27 had COPD only and 13 were used as Controls. NTHi was detected in the lower airways of all three groups (Lung Cancer 20%; COPD 22% and Controls 15%). Total IgE was highest in Lung Cancer subjects followed by COPD and control subjects (mean ± SD: 870 ± 944, 381 ± 442, 159 ± 115). Likewise total IgG was higher in Lung cancer (Mean ± SD: 6.99 ± 1.8) patients compared to COPD (Mean ± SD: 5.43 ± 2). Conclusions: The lack of difference in NTHi and specific antibodies between the three groups makes it less likely that NTHi has an important pathogenetic role in subjects with Lung Cancer. However the detection of higher IgE antibody in Lung Cancer subjects identifies a possible mechanism for carcinogenesis in these subjects and warrants further study.